Nanopowder synthesis of aluminum doped cadmium oxide via sol–gel calcination processing - Aydın, Cihat; El- Nasser, H. M.; Yakuphanoğlu, Fahrettin; Yahia, I. S.; Aksoy, M. (My University, 2011)
The structural, optical and electrical properties of undoped and Al-doped CdO powder nanostructures prepared by sol–gel calcinations method have been investigated. X-ray diffraction (XRD) results revealed that pure and Al-doped CdO have the polycrystalline with face centered cubic (FCC) structure. The crystallite size for undoped and 5, 10, 15, 20% of Al-doped CdO samples were found to be 17.2, 15.9, 16.1, 16.3 and 16.8 nm, respectively. The optical band gap of the samples were determined from the diffused reflectance spectra and Eg values for undoped and 5, 10, 15, 20% of Al-doped CdO samples were found to be 1.89, 2.07, 2.03, 2.07 and 2.12 eV, respectively. The electrical conductivities of pure and Al-doped CdO were measured in the temperature range (290–420 K) and their temperature dependence was analyzed according to Arrhenius relation. The electrical conductivity results indicate that the electrical conductivity mechanism is controlled by thermally activated processes. The results showed that sol–gel calcinations technique can be effectively used to produce undoped and doped nanopowders.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pure and Al-doped CdO nanostructure; Sol–gel; Diffused reflectance; Optical band gap; Dc electrical conductivity